WHAT MAKE EMPLOYEES STAY? CASE STUDY OF EMPLOYEE ENGAGEMENT IN MALAYSIA CHILDCARE CENTRE - Meng,Chan, Ling-; Durai, Thamil; Lau Say Min, Claudia,; Jaganathan, Mathivannan; Koay, Ying-Yin, (International Journal of Psychosocial Rehabilitation, 2020)
This study intended to examine the influences of perceived organisational support and rewards on employee engagement in the childcare centre in Malaysia. Subjects in this research study consist of 300 caregivers in a childcare centre in Selangor, Malaysia. The finding indicated that positive perceived organisational support bring positive influences on employee engagement at the workplace. When an individual perceived higher level of organisational support, they will be willing to incorporate more effort and engage with the organisation. Besides that, the satisfaction of employee’s self needs with both intrinsic and extrinsic rewards provided by the employer will bring positive influences on employee engagement. This research recommends that future researchers investigate other possible motivational factors influencing the employee engagement in this industry, such as training and development, job security and career development. The management of childcare centre could place more attention on planning and increasing employee belongingness via fulfilling their individual needs and provide both emotional and social support towards them. In order to enhance employee engagement among the child caregiver, organisations should revise the basic salary and enhance the benefits packages for them, in order to fulfil their basic needs and improve their satisfaction towards their job and the organisations. Through the study, it implies that the higher the employee engagement with the organisation, the better the performance of them in the organisation, with the presence of positive motivation elements, such as positive organisational support and attractive rewards. This study intended to examine the influences of perceived organisational support and rewards on employee engagement in the childcare centre in Malaysia. Subjects in this research study consist of 300 caregivers in a childcare centre in Selangor, Malaysia. The finding indicated that positive perceived organisational support bring positive influences on employee engagement at the workplace. When an individual perceived higher level of organisational support, they will be willing to incorporate more effort and engage with the organisation. Besides that, the satisfaction of employee’s self needs with both intrinsic and extrinsic rewards provided by the employer will bring positive influences on employee engagement. This research recommends that future researchers investigate other possible motivational factors influencing the employee engagement in this industry, such as training and development, job security and career development. The management of childcare centre could place more attention on planning and increasing employee belongingness via fulfilling their individual needs and provide both emotional and social support towards them. In order to enhance employee engagement among the child caregiver, organisations should revise the basic salary and enhance the benefits packages for them, in order to fulfil their basic needs and improve their satisfaction towards their job and the organisations. Through the study, it implies that the higher the employee engagement with the organisation, the better the performance of them in the organisation, with the presence of positive motivation elements, such as positive organisational support and attractive rewards